2021
DOI: 10.1093/rheumatology/keab210
|View full text |Cite
|
Sign up to set email alerts
|

Limited sensitivity and specificity of the ACR/EULAR-2019 classification criteria for SLE in JSLE?—observations from the UK JSLE Cohort Study

Abstract: Objectives This study aimed to test the performance of the “new” American College of Rheumatology (ACR) and European League Against Rheumatism (EULAR) criteria, that include anti-nuclear antibodies (ANA) positivity as entry criterion, in juvenile-onset systemic lupus erythematosus (jSLE). Methods Performance of the ACR/EULAR-2019 criteria were compared with Systemic Lupus International Collaborating Clinics (SLICC-2012), usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The EULAR/ACR-2019 criteria may miss a signi cant proportion of jSLE patients, mostly because of the absence of ANA positivity. On the other hand, positive ANA can be found in a variety of autoimmune diseases, which may result in misclassi cation as SLE based on the new criteria [14]. Within ANA-positive jSLE patients, the sensitivity of the EULAR/ACR criteria was higher (99.5%), but the speci city dropped to 75.9%, signi cantly lower than the results (98.4%) of Ma et al [12].…”
Section: Discussionmentioning
confidence: 71%
“…The EULAR/ACR-2019 criteria may miss a signi cant proportion of jSLE patients, mostly because of the absence of ANA positivity. On the other hand, positive ANA can be found in a variety of autoimmune diseases, which may result in misclassi cation as SLE based on the new criteria [14]. Within ANA-positive jSLE patients, the sensitivity of the EULAR/ACR criteria was higher (99.5%), but the speci city dropped to 75.9%, signi cantly lower than the results (98.4%) of Ma et al [12].…”
Section: Discussionmentioning
confidence: 71%
“…However, they stated that the performance of the 2019 criteria in the youth population can be improved if they are classified using 13 points and not 10 as originally proposed. Other recent studies do not find differences between the three criteria (EULAR/ACR 2019, SLICC 2012, and ACR 97) [ 31 ]. However, this contrasts with data published by Levinsky et al [ 28 ] who documented a better sensitivity of the EULAR/ACR 2019 with respect to the SLICC 2012 in a population with juvenile SLE.…”
Section: Discussionmentioning
confidence: 95%
“…Smith et al. [ 12 ] found that a subset of patients presenting with organ damage including biopsy of class III/IV was ANA-negative with half eventually developing ANA-positivity. The authors speculate that ANA-negativity, particularly in young SLE patients, may be related to genetic factors that contribute to the inflammation and tissue damage in the absence of autoantibodies.…”
Section: Discussion/conclusionmentioning
confidence: 99%